(untitled) (ModaPalavra e-periódico, 2020)
This article aims to explore the connections between the corset and fetishism in the nineteenth century and the beginning of the twentieth century. Supported by the perspective of Anne McClintock on Imperial Leather: Race, Gender and Sexua lity in the Colonial Contest (2010), in regards to fetish and the class and gender dynamics, this articled analyzed the prominence of the corset in the maintenance of Victorian female domestic idleness. The scrutiny suggests the crisis of value conducted b y the conflict among public and private spaces, by the connection among male agency, female stagnation and the impossibility of pleasure from female idleness are all embodied in the corset, which converts it into an object of fetishism. The recovery of the writings of Freud, the study of the genealogies of fetishism and the resumption of its etymological origin broadens the meaning of perspectives for the relation between the corset and the nineteenth century - female body, whose silhouette, drawn by corsetry , delimited measuredly its possibilities in its social role.